Simulation and Experimental Study on the Shrub-Cutting Performance of Quasi-Planetary Cutter - Zikai Song; Xibin Dong; Chi Teng; Ben Guo; Jiawang Zhang; Yuchen Zhang (Applied Sciences)
To evaluate the performance of quasi-planetary cutting tools, three shrubs were selected and studied using a combination of numerical simulation and cutting test bench experiments. Based on the constitutive model of shrub material and LS-DYNA simulation, the effects of tool speed (n), feed speed (v), and shrub diameter (Da) on peak cutting force (Fmax) and peak cutting power (Pmax) were analysed through a single-factor simulation test. Using the shrub-cutting test bench, an orthogonal test was designed with n, v, and moisture content (w) as factors and Fmax and Pmax as indicators. A regression model was established, and a single-factor comparison test for w was conducted. The results indicate that Fmax decreases as n increases, while Pmax initially decreases and then increases. Both Fmax and Pmax increase with rising v and Da. As w increases, Fmax and Pmax first decrease and then increase. When n is 1813 r/min, v is 30 mm/s, and w is 10.9%, Fmax and Pmax reach their optimal values of 8.42 N and 282.99 W, respectively, with verification test errors of 2.68% and 1.56%. The findings provide methodological and data support for studying the cutting performance of new cutting tools.